A time-series study of percutaneous closure of patent foramen ovale: premature adoption?. Issue 1 (4th January 2016) - Lew, Kian Nian; Angelini, Gianni D; Hollingworth, William
Abstract : Objectives: To evaluate the impact of National Institute for Health and Care Excellence (NICE) guidance in January 2005 and subsequent trial evidence on the adoption of percutaneous closure of patent foramen ovale (PCPFO). Methods: A retrospective time series study was conducted using the Inpatient Hospital Episode Statistics (HES) England. A total of 3801 patients, aged ≥18 and ≤60 years, who had PCPFO from 1 April 2006 to 31 March 2012 in England. Percentage change annualised (PCA) in PCPFO procedure rates between initial NICE guidance and publication of trial results was analysed. Results: Between Quarter 2, 2006 and Quarter 4, 2009, 2163 PCPFO procedures were performed, with an increasing PCA of 48.4%. The procedure rate peaked before the presentation of equivocal results from the first randomised controlled trial (RCT) in late 2010, and declined between Quarter 4, 2009 and Quarter 4, 2011 (PCA=−15.3%). Of more than 2300 patients recruited to three RCTs, only 71 were recruited in English hospitals. Conclusions: PCPFO was rapidly adopted after the publication of initial NICE guidance despite the absence of RCT evidence of efficacy. Very few English patients participated in international RCTs of PCPFO, suggesting that NICE recommendations also failed to encourage the generation of RCT evidence.